Kencana Ungu (Ruellia tuberosa L.): Botani, Fitokimia Dan Pemanfaatannya Di Indonesia - Sulis Stiya Wati; Anisatu Z. Wakhidah (Indobiosains, 2023)
Kencana ungu (Ruellia tuberosa L.) or commonly known as pletekan flower, one of the flowering plants that classified tp Acanthacea family. This plant grows a lot on the sides of the road, bushes, in the meadows, or around the rice fields. Kencana ungu (Ruellia tuberosa L.) contains a lot of phytochemicals that potentially provides some benefits for the community. However, the influence of modernization has resulted in humans preferring not to use wild plants as herbal medicines. A literature review is needed to document previous research regarding the medicinal potential of this plant. The phytochemical content of Kencana ungu includes anthocyanin pigment type malvidin which is located in the flower. This pigment can be used to dye clothes, The others phytochemicals are alkaloids, flavanoids, triterpenoids, steroids and saponins. The bioactivity performed by Ruellia tuberosa L. around antidiabetic, antifungal, antioxidant, anticancer, and antibacterial. Several regions in Indonesia use this plants as a diabetes drug, such as Southeast Sulawesi and West Java. In Indonesia, this plant is used as herbal medicine which is used to cure various diseases.